Experimental study on damage evolution of rock under uniform and concentrated loading conditions using digital image correlation. Issue 8 (27th March 2013) - Song, H.; Zhang, H.; Fu, D.; Kang, Y.; Huang, G.; Qu, C.; Cai, Z.
ABSTRACT: Damage evolution and crack propagation in sandstone specimens have been observed by digital image correlation method. To investigate deformation and failure process of rock under different loading conditions, uniaxial compression and indentation tests were performed. Through the experiment, displacement and strain fields are simultaneously obtained that can visually display the distribution, mode and evolution of deformation and cracking in rock. Experimental results show that the damage distributes diffusely in rock at early loading stage, and the measured apparent strain increasingly concentrates with loading because of the nucleation of crack; propagation of the crack leads to the eventual failure of the specimen. Damage factor is calculated on the basis of deviation of apparent strain, and localization factor is presented to describe the level of deformation localization. The combined use of two factors can well represent the damage evolution of rock under compression.